Single-Cell protein for feed and food - Ledbetter Fred (The EuroBiotech Journal)
As global demand for protein sources continues to rise due to increasing populations and changing dietary preferences, the shortage of conventional protein for feed and food poses significant challenges for food security. Single-cell protein (SCP), derived from microorganisms such as yeasts and bacteria, represents a promising alternative to traditional protein sources. Among these, methanotropic bacteria such as Methylococcus sp. and Methyocystis sp. can provide protein from methane as their sole carbon and energy source. Oleaginous yeasts like Yarrowia lipolytica are gaining attention in animal nutrition, particularly chicken and aquaculture, since they not only contain protein but also lipids. Yarrowia lipolytica, which comprises approximately 20% lipids by cell weight, can effectively supplement protein in animal diets, improving feed efficiency and average daily gain (ADG). Incorporating 3% of this yeast instead of soybean meal can enhance growth performance, while higher inclusion rates may lead to adverse effects such as diarrhea in animals like piglets due to increased lipid content and reduced nutrient digestibility. The thick cell wall of Yarrowia lipolytica can limit nutrient absorption, indicating that lysis of the yeast cell walls may be necessary to optimize nutrient release. Additionally, the use of another oleaginous yeast, Lipomyces starkeyi, has demonstrated potential as a viable substitute for vegetable oils in fish diets, maintaining growth and meat quality without negative impacts. Research indicates that SCP can constitute significant portions of nitrogen intake in livestock, supporting performance without inducing adverse heat production. These findings underscore the potential of SCP and oleaginous yeasts in addressing protein shortages while promoting sustainable practices in animal nutrition. However, further studies are essential to optimize their utilization in various dietary formulations.